An Update of Synthetic Approaches and Structure‐Activity Relationships of Various Classes of Human MAO‐B Inhibitors. Issue 7 (11th February 2021) - Sharma, Pratibha; Singh, Manjinder; Mathew, Bijo
Abstract: The selective MAO‐B inhibition is greatly influenced by the degradation pathways of various biogenic amines. So the design and development of diverse class of MAO‐B inhibitors are considered as an effective adjuvant therapy of various neurodegenerative disorders. Recent studies documented that introduction of an electron rich linker between two aryl or heteroaryl rings explored as a promising structural framework of the inhibition of MAO‐B. The electrophilicity and flexibility character of the linker can anchor different orientation of binding mode in both entrance and substrate cavity of MAO‐B. The current review focus on the design aspect, synthetic route and structure activity relationships (SARs) various class of selective MAO‐B inhibitors like chalcones, coumarins, chromones, pyrazolines, xanthines, isatins, FDA approved analogs etc. Abstract : The selective MAO‐B inhibition is greatly influenced by the degradation pathways of various biogenic amines. So the design and development of diverse class of MAO‐B inhibitors are considered as an effective adjuvant therapy of cognitive disorders like Alzheimer's disease (AD) and Parkinson's disease. The current review focus on the design aspect, synthetic route and structure activity relationships (SARs) various class of selective MAO‐B inhibitors like chalcones, coumarins, chromones, pyrazolines, xanthines, isatins, FDA approved analogs etc.